Antigen-G of Larva Serum of Musca domestica as an Immunoglobulin Production Promoter in Goats under an Organic Maintenance - Laurentius Rumokoy; Hengky Kiroh; Ivonne Maria Untu; Geertruida Assa; Santie Turangan; Wisje Lusia Toar (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2020)
This experiment aimed to reveal the effect of serum G-antigen of M. domesticainsect larvae (LAS) as promoter antigen on serum immunoglobulin production in organically managed goat livestock. This study used 12 local goats which were divided into two groups: as a control group and treated group receiving treatment. Insect rearing was conducted to obtain the larvae, the antigen-G was then extracted from the larvae to be used as promoter antigen to enhance the serum antibody production which was subcutaneously immunized in experimental goats and incubated for a period of 14 days. Blood collection of 2.5 ml was taken through the jugular vein and then carried out a quantification of serum protein level indicating the antibody proportion of goats. The data of the LSA extract proportion level were statistically analyzed with t-test, and the quality classification level of serum immunoglobulin of animal groups were statistically analysed. The results showed that the serum of animal treated with LSA of M. domesticaresulted in a higher level of immunoglobulin (P <0.01) compared to the control. We conclude that the antigen-g substance (LSA) could support the efforts to improve the production of organic goat livestock by increasing the total level of antibodies circulating in the blood.